Relationship between vertical jump performance during different training periods and results of 200m-sprint - Siembida, P.; Zawadka, M.; Gawda, P. (Baltic Journal of Health and Physical Activity, 2021)
Background: The purpose of the current study was to investigate: (1) differences between three types of countermovement jumps (CMJ), (2) development of lower-body strength during training periods, and (3) relationship between 200m personal best results and jumping ability in sprinters. Material and methods: A total of 14 male sprinters from local university academic sport club participated in the study. Athletes performed three variants of CMJ: with arm swing (AS), without AS, and from a maximal squat position. We took measures two times: during the active rest period and the final phase of the preparatory period. For measurements the Optojump photoelectric cell system was used. Statistical significance was set at p = 0.05. Results: Effect of the training period and jump variant was shown on all jump parameters (height, total energy, and specific energy; p<0.001). Personal best 200m time was significantly correlated only with total energy in both training periods in all jump variants. Conclusions: According to the results obtained in this study, we conclude that: (1) jumping parameters depends on CMJ variants, (2) jumping abilities improved during sprinter training, (3) 200m-sprint PB are related to total energy, but not with specific energy and jump height.